INTERAKSI NASIONAL PADA ERA DIGITAL : ANALISIS PERAN BUDAYA SEKOLAH DALAM MENANAMKAN NILAI KEBHINEKAAN DI SDIT AL-HISA KOTA PEKANBARU - M. Muda; Anwar, Khoirul; zulhidah, Zulhidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The digital era presents significant challenges to national integration, particularly in shaping the character of elementary school students who are highly exposed to global information and potential echo chambers. This study aims to analyze the role of school culture in instilling diversity and national integration values at SDIT Al-Hisa Pekanbaru amidst digital disruption. Using a qualitative case study approach, data were collected through in-depth interviews with principals and teachers, participant observation, and documentation. The results indicate that SDIT Al-Hisa Pekanbaru integrates national integration values into its school culture through three main strategies: (1) habituation of inclusive religious and national rituals, (2) digital literacy-based project learning that promotes local wisdom, and (3) the integration of moderate Islamic values (Wasathiyah) with Pancasila. School culture acts as a filter and accelerator, ensuring that students not only maintain their religious identity but also possess a strong national character in navigating the digital era. This study concludes that a synergy between Islamic values and national diversity, facilitated by digital literacy, is crucial for elementary education.